Baltoscandian conodont biofacies fluctuations and their link to Middle Ordovician (Darriwilian) global cooling. (16th January 2018) - Rasmussen, Jan A.; Stouge, Svend
Abstract: The Middle Ordovician conodont genera that are suitable for palaeoenvironmental interpretations from the epicontinental Baltoscandian platform have been identified and evaluated to establish and describe conodont biofacies and their relationship to global cooling. The construction of biofacies was based on multivariate statistical analyses of more than 375 700 conodont specimens from 520 samples and 21 localities across Baltica. Three distinct, recurrent and laterally extensive conodont biofacies existed across the Baltoscandian platform of the Baltica continent during the Dapingian and early to middle Darriwilian stages (Middle Ordovician). A relatively shallow water conodont assemblage named the Baltoniodus–Microzarkodina Biofacies characterized the inner shelf localities in central Sweden, Estonia, Russia and Ukraine. In the distal shelf areas, patterns are more complex. Here, genera of the Periodon Biofacies characterized the shelf margin areas of the Scandinavian Caledonides facing the relatively warm Iapetus Ocean towards the north, whereas the Protopanderodus Biofacies dominated the distal shelf areas facing the cooler Tornquist Sea towards the south‐west. Although these three main biofacies continued to dominate during the succeeding Darriwilian stage, distinct changes in the distribution of biofacies took place during the transition from the Dapingian Stage to the Darriwilian. We argue that the biofacies change was triggered by a regressive event related to early Darriwilian cooling, and that the palaeoclimatological changes influenced the Baltic conodont faunas near the Tornquist Sea margin before those of the Iapetus margin (early vs middle Darriwilian).